Penggunaan Huruf Maa dan Laa Sebagai Pembentuk Makna Dalam Kitab Al-Arba’in An-Nawawiyyah - Dontili, Kholila; Fatoni, Ahmad Sirfi (Journal of Arabic Language Studies and Teaching, 2025)
This study aims to examine or analyze the use of the letters maa and laa in the book of Al-Arba'in an-Nawawiyyah, especially in the formation of negation and affirmation meanings in the hadith text. This study was conducted using the approach of nahwu science to understand the special function of the two letters in the structure of Arabic sentences. The results of the study show that the letter maa in the book of al-Arbain an-Nawawiyyah functions as a tool of negation, limitation, and affirmation. At the same time, the letter laa is used as an explicit negation or as a strict prohibition. An in-depth analysis of its use in the book of al-Arba'in an-Nawawiyyah shows the important role of both in strengthening the moral and legal messages of Islam conveyed by the Messenger of Allah. By understanding the function of maa and laa, readers can avoid misunderstandings in interpreting the teachings of Islam contained in the hadith of al-Arba'in an-Nawawiyyah, as well as enriching readers' insights into the rules of nahwu in the study of religious texts.